2022
DOI: 10.1186/s40001-022-00689-w
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological agents for the prevention of colistin-induced nephrotoxicity

Abstract: Background Colistin is a polymyxin antibiotic which has been used for treatment of Gram-negative infections, but it was withdrawn due to its nephrotoxicity. However, colistin has gained its popularity in recent years due to the reemergence of multidrug resistant Gram-negative infections and drug-induced toxicity is considered as the main obstacle for using this valuable antibiotic. Results In total, 30 articles, including 29 animal studies and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 130 publications
1
15
0
Order By: Relevance
“…In this study, the biochemical and histopathological studies indicated that colistin nephrotoxicity was associated with a reduced glomerular filtration rate and collagen deposition. This is in line with the reported marker of colistin nephrotoxicity [ 21 , 22 ]. Interestingly, omeprazole alleviated such markers, thereby confirming its protective activity.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the biochemical and histopathological studies indicated that colistin nephrotoxicity was associated with a reduced glomerular filtration rate and collagen deposition. This is in line with the reported marker of colistin nephrotoxicity [ 21 , 22 ]. Interestingly, omeprazole alleviated such markers, thereby confirming its protective activity.…”
Section: Discussionsupporting
confidence: 91%
“…If it is necessary to use drugs with significant potential nephrotoxicity, detailed recommendations are developed to prevent their harmful effects on the kidneys. For example, reference can be made to the prophylactic use of antioxidant compounds (vitamin E, vitamin C, flavonoids, melatonin, N-acetylcysteine, luteolin, lycopene, or coenzyme Q10) that reduce free radical damage in the course of the use of drugs that increase oxidative stress in kidney tissues, e.g., during treatment with vancomycin [ 101 ], cyclophosphamide [ 102 ], colistin [ 103 ], cyclosporine A [ 104 ], tacrolimus [ 105 ], contrast media [ 106 ], and cisplatin [ 107 ]. Antioxidants, vitamins, and minerals were also demonstrated to prevent gentamicin-induced nephrotoxicity [ 108 ].…”
Section: Preventive Factors Of Drug-induced Nephrotoxicitymentioning
confidence: 99%
“…Unfortunately, very few clinical trials have been performed to guide this therapy, and most studies used animal models or in silico models. A recent review by Mirjaili et al [40] highlighted methods performed to reduce colistin nephrotoxicity.…”
Section: Antibioticsmentioning
confidence: 99%